Implementasi sistem manajemen anti penyuapan dalam mewujudkan good governance pada Pengadilan Agama Bantul - Muhammad Iqbal Fanani; Uun Sunarsih (Jurnal STEI Ekonomi, 2025)
The handling of corruption has been extensively carried out by the Indonesian government through a series of policies. Corruption incidents are closely related to the associated risk of bribery. The risk of gratification/bribery has become a dominant form of corruption in Indonesia, and this issue also occurs within the judicial system. The Bantul Religious Court is one of the units under the Supreme Court that took the initiative and volunteered to implement the Anti-Bribery Management System (ABMS) of the Supreme Court in 2023. This research aims to reveal the implementation of ABMS at the Bantul Religious Court and its impact on fulfilling the principles of Good Governance. The research method used is qualitative ethnomethodology, focusing on routine activities and emphasizing the observation of the daily interactions of a group of people within a community. The success of the Anti-Bribery Management System depends on the motivation and background of its needs, as well as the commitment of all parties, especially leaders, who must have a forward vision and a focus on improving public services. Understanding risk management remains a challenge, requiring sufficient planning and resources. The implementation of ABMS by the Supreme Court of Indonesia benefits society by reducing bribery and gratification practices through the improvement of work processes and risk management, enhancing effectiveness, accountability, and inclusivity in good governance. Article Information:Received 8/14/2024 | Revised 10/18/2024 | Accepted 11/30/2024 | Online First 1/19/2025